Influence of mother tongue on English writing : an error-analysis study about Grade 9 students in Pakistan - Malik, Muhammad Abid; Azam, Tayyaba; Pathan, Habibullah; Khatoon, Sahib (Penerbit Universiti Kebangsaan Malaysia, 2022)
The influence of the mother tongue on second language acquisition is well-known. Pakistan is a multi-lingual country with scores of mother tongues, yet their influence on English language writing has not been investigated properly. This error-analysis study contributes in this regard by finding out syntactical and semantical errors committed by Pakistani students with different mother tongues. It also investigated if there were any patterned differences or similarities in error-making. Data was collected from one hundred grade 9 students from a public school in Islamabad. They belonged to five different mother tongue groups i.e. Punjabi, Pashto, Urdu, Hindko and Potohari. The findings showed that generally all five groups committed more syntactical errors than semantical ones. Overall, they were most vulnerable in tense, spelling and subject-verb-agreement. Four of those groups (Punjabi, Pashto, Urdu and Hindko) showed similar performance with a range of 4.18-5.34 in syntactical, 3.61-4.25 in semantical, and 8.41-9.25 in total errors. Potohari group committed twice as many errors as any other group. The study recommends that while developing the teaching materials and assignments, teachers should consider the special needs of different mother tongue groups. Furthermore, special attention should be paid to Potohari group by providing them with extra English classes and materials.